PERAN KOMUNIKASI ANTRPERSONA DAN KINERJA APARATUR PEMERINTAH DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DESA SUNGAI KAYU KECAMATAN KAPUAS BARAT KABUPATEN KAPUAS - Lisnawati Lisnawati; Ma'ruf Abdullah; Zain Noknah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Interpersonal communication is very important in an organization. The interpersonal communication within an organization is often ineffective due to inefficient communication that can lead to misunderstand the meaning of the message. The success or failure of an organization is determined by all the elements that exist within the organization, all of it is inseparable from the well-established interpersonal communication that exists both in every village officials and the public.The role of interpersonal communication and the performance of the village officials are very important in supporting a village development, especially the construction of the roads or bridges in Sungai Kayu village, hence the author interested in researching with a title “The Role of Interpersonal Communication and The Performance of The Village Government Officials Towards The Infrastructure Development of Sungai Kayu Village West Kapuas Sub-district Kapuas District”.The research was conducted in RT.4, RT.5 and RT.6 of Sungai Kayu Village West Kapuas Sub-district Kapuas District in May 2013. The approach method used was a quantitative of all the data collected from 139 respondents analyzed in descriptive using a percentage technique.The analysis result of partial significance for all variables was 73.27%, thus the role of interpersonal communication and the performance of the village government officials towards the infrastructure development of Sungai Kayu Village West Kapuas Sub-district Kapuas District have been categorized achieved with indicators: X1 (the interpersonal communication), X2 (the performance of village government officials) and the dependent variable Y are the dependent variables. Therefore, this research is expected to improve the interpersonal communication better among the villagers and between the villagers and the village officials, besides this research can also improve the performance of the village officials especially in the development of both physical and nonphysical. Keywords : Interpersonal Communication, Performance of village government Officials